Algoritma, Buzzer, dan Viralitas Isu Agama: Studi tentang Polarisasi dalam Komunikasi Politik Islam - Muh. Wisnul B. Pamus Wisnul; Haidir Fitra Siagiaan (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2026)
The development of digital technology has fundamentally transformed the practice of Islamic political communication, particularly through the emergence of algorithm-based social media. This article aims to analyse the interrelationship between media algorithms, the ‘buzzer’ phenomenon, and the virality of religious issues in shaping polarisation amongst the Muslim community. This research employs a qualitative approach using a literature review method, examining various recent literature in the fields of political communication, digital media, and Islamic studies. The findings indicate that social media algorithms are not neutral; rather, they reinforce users’ preferences through content selection mechanisms that have the potential to create echo chambers. In this context, ‘buzzers’ act as strategic actors who construct narratives and mobilise public opinion, whilst the virality of religious issues accelerates the spread of collective emotions that are often not balanced by information verification. These three factors simultaneously contribute to increasing social polarisation, the fragmentation of the Muslim community, and the weakening of the quality of religious discourse. This article emphasises the importance of media literacy and the internalisation of Islamic communication ethics as a means of mitigating the negative impacts of digital political communication.